Implementación y fortalecimiento de potencialidades ambientales mediante la aplicación de educación ambiental en la I.E Clemente López - Aguila Mejía, Margarita Merisbeth Del (2013)
Engineer has as title "Implementation and strengthening of environmental potentials by means of the application of environmental education in the Educational Institution "Clemente Lopez Montalván", Calzada 2010. lt considers to establish the environmental initial and final diagnosis in the topics of water, soil, air, flora and fauna; to implant as environmental potential the segregation of solid residues and also to constitute as environmental potential the creation of an environmental club integrated by the own students. This work focused on the implementation of the Environmental Education Program - EEP, with the aim of increasing the students knowledge of secondary education in the enviromnental aspect; to meet the objectives used methodology and techniques of education that helped in the teaching-learning process as the development of educational materials for each topic, dynamics in groups, field tJips in order to achieve the awareness of students. The study was conducted with 62 students, 30 students from the 1st grade "B" and 32 students of the 2nd grade "A" of the secondary level of the Educational Institution "Clemente Lopez Montalván" of Calzada distJict. In the results of the investigation it was possible to establish that, in the initial survey before the PEA application to it climbs of O - 1 O (learning in beginning), exist 1 O % of students in the 1 o "B" and 12.5% in 2 o "A" and between 90% to 87.5% of knowledge respectively. And in the fmal survey after the PEA to a scale of O - 10 (learning in beginning), there was no student in the 1 o "B" and 2 o "A", achieving 100 % of passes in both sections with regard to the knowledge of the water topics, soil, air, flora and fauna; result that allows us to affmn the success ofthe PEA in the immersed sections in the present study. As we demonstrated in the hypothesis test in our work the knowledge of the students increased in the 5 topics covered in the classroom according to the schedule of work. The implementation of Environmental Education influences the implementation and strengthening of potential environmental educational institution in the "Clemente Lopez Montalván"- Calzada, 2010. On the other hand, was implemented and strengthened environmental potential as the segregation of solid waste through theoretical workshops - practica! in the educational institution, making the deployment of 6 containers of 80 liters and 6 containers of 20 liters, in the colors (yellow, green and blue) to identify and classify the sol id waste ( see photo No # O 1 ). There was constituted the environmental club called: " Y oung students joined to preserve the nature" (JOESUCNA) shaped by students ofthe 1 o "B" and 2 o "A", with whom one was employed at equipment as for conservation at the district of Causeway, (to see Proved). Key words: educational institution, environmental club.